Research on a Fiber Optic Oxygen Sensor Based on All-Phase Fast Fourier Transform (apFFT) Phase Detection - Xia, Pengkai; Zhou, Haiyang; Sun, Haozhe; Sun, Qingfeng; Griffiths, Rupert (Sensors (Basel, Switzerland), 2022)
Fiber optic oxygen sensors based on fluorescence quenching play an important role in oxygen sensors. They have several advantages over other methods of oxygen sensing—they do not consume oxygen, have a short response time and are of high sensitivity. They are often used in special environments, such as hazardous environments and in vivo. In this paper, a new fiber optic oxygen sensor is introduced, which uses the all-phase fast Fourier transform (apFFT) algorithm, instead of the previous lock-in amplifier, for the phase detection of excitation light and fluorescence. The excitation and fluorescence frequency was 4 KHz, which was conducted between the oxygen-sensitive membrane and the photoelectric conversion module by the optical fiber and specially-designed optical path. The phase difference of the corresponding oxygen concentration was obtained by processing the corresponding electric signals of the excitation light and the fluorescence. At 0%, 5%, 15%, 21% and 50% oxygen concentrations, the experimental results showed that the apFFT had good linearity, precision and resolution—0.999°, 0.05° and 0.0001°, respectively—and the fiber optic oxygen sensor with apFFT had high stability. When the oxygen concentrations were 0%, 5%, 15%, 21% and 50%, the detection errors of the fiber optic oxygen sensor were 0.0447%, 0.1271%, 0.3801%, 1.3426% and 12.6316%, respectively. Therefore, the sensor that we designed has greater accuracy when measuring low oxygen concentrations, compared with high oxygen concentrations.